PENGEMBANGAN USAHA HORTIKULTURA PETANI KECIL - MADE ANTARA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Bali still has big potency to develop of fruits horticulture through the effortintensification. This matter is supported by: (i) availability of dry land of 126.487 ha can becultivated intensively, availability of rice field of 87.765 ha can be cultivated for horticulturerotating, high land fertility and specific, agroclimate suited for development varioushorticulture crop type, (ii) Bali has potency of human resources and labor abundant; (iii) Balihas social capital in the form of experience of farmer in farming and system social of Balipeople easy to make group as diffusion media for innovation and technology, and (iv)Indonesia generally and Bali specially have four excess of nature which not have by mostdeveloped nations that is, length and intensity of irradiation, favourable temperature, freetyphoon, and rainfall which enough.To developt the small businessman horticulture, so strategy able to do better throughthree step those are: (i) redistribution of main production asset like the agriculture land, can inthe form of transfer of ownership or in the form of institutional arrangement which giveopportunity to land poor farmer; (ii) increase the agriculture land productivity, pass change oftechnology and innovation, policy of economics and improve of institutional system, and (iii)investment in human resources through training and education purpose increase theknowledge and skill of horticulture farmer and agriculture government officer.To reach the high competitiveness of Bali horticulture products specially andIndonesia generally is by applying concept of agribusiness system, that is integratingsubsystem of production with upstream and downstream agriculture industry, subsystem ofmarketing or commerce and subsystem of supporting institution. Beside that, removingconstraints of substance and organization faced by small farmer and also increasing role ofgovernment and other relevant institution in facility and to control (not to regulate)development of horticulture business.To reach success development of horticulture business in Bali specially and inIndonesia generally, please learn from successful story of Thailand agribusiness development.Successfulness of products exporting of Thailand agribusiness horticulture is result of year’shard work which involves much side, from king/queen until worker agribusiness, fromlecturer/researcher until public society, and from government/financial institution untilentrepreneur. Successful story of Thailand expected can become inspiration, lesson andconsideration for Indonesia in the plan and execution of horticulture agribusinessdevelopment which orientation for global market, which is finally will positive affect towardincreasing the prosperity of society in general and small businessman of horticulture specially.